The Oxford dictionary of philosophy - Blackburn, Simon (Oxford Oxford University Press, 1994)
Up-to-date dictionary of philosophy with 2,500 entries covering the entire span of the subject and nearly 500 biographical entries.
Preface, v-vii -- Dictionary, 1 -- Appendix: Logical Symbols, 406-408.
Keywords: Philosophy -- Dictionaries